1998
DOI: 10.1128/jvi.72.11.9166-9172.1998
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Herpes Simplex Virus Type 1 DNA in Chronic Conjunctival and Eyelid Lesions of Mice

Abstract: Herpes simplex virus type 1 (HSV-1) causes chronic blepharitis and conjunctivitis as well as keratitis in humans. The pathogenesis of these inflammatory ocular and dermal lesions is not well understood. We have examined the persistence of HSV-1 DNA and its relationship to inflammatory lesions in the conjunctiva and eyelid skin of mice which were inoculated with HSV-1 by the corneal route. Viral DNA was detected by in situ PCR in the conjunctiva and eyelid tissue of infected mice at 5, 11, 23, and 37 days posti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 34 publications
(51 reference statements)
0
17
0
Order By: Relevance
“…PRV DNA was consistently detected in some studies (5,9,35,36) but not others (3,18). Nonneural sites for latency or persistence have also been described for HSV-1 (8,17,29) and may be important for ocular disease (17). Thus, nonneural sites of latency or persistence may be a normal outcome of acute infection by certain ␣-herpesviruses.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…PRV DNA was consistently detected in some studies (5,9,35,36) but not others (3,18). Nonneural sites for latency or persistence have also been described for HSV-1 (8,17,29) and may be important for ocular disease (17). Thus, nonneural sites of latency or persistence may be a normal outcome of acute infection by certain ␣-herpesviruses.…”
Section: Discussionmentioning
confidence: 98%
“…Canine herpesvirus 1 DNA has been detected in tonsils of latently infected dogs (6), and during reactivation virus was recovered from tonsil tissues (20). HSV-1 has been detected in bone marrow of humans (8) and in other nonneural sites in small-animal models (17,29). Pseudorabies virus (PRV) DNA has also been detected in tonsils (2,3,16,35,36) of latently infected swine.…”
mentioning
confidence: 99%
“…We next studied the effect of HSV DNA on TLR gene expression in corneal cells, because HSV DNA is detected in patient corneas even in the chronic or silent stages of infection. In this experiment, we used McKrae and MP DNA, because both strains are pathogenic in the cornea (Wander et al, 1980;Centifanto-Fitzgerald et al, 1982) and KOS DNA does not persist long in HSK corneas (Maggs et al, 1998). When HCEs were transfected with McKrae or MP DNA, gene expression of TLR-3 was enhanced by 3?7 and 226, respectively, compared with untransfected cells (Fig.…”
Section: Induction Of Tlr-3 and -9mentioning
confidence: 99%
“…60 In a mouse model, viral replication was shown to be necessary for the development of HSK, 60 and, in other studies, HSV-1 was found to persistently infect the conjunctiva, eyelid skin, and cornea of mice. 61,62 In cats with FHV-1-induced stromal keratitis, Nasisse et al 63 observed the presence of viral antigen and infiltrating mononuclear cells in the corneal stroma, compatible with an immunopathologic mechanism.…”
Section: Prevalence Of Fhv-1mentioning
confidence: 99%